Applications of Mechanochemistry for the Synthesis of DNA on Ionic Liquid Supports. Issue 8 (5th May 2021) - Johnston, Christopher; Hardacre, Christopher; Migaud, Marie E.
Abstract: The standard methodology for the synthesis of oligonucleotides is the solid‐phase method. Here, we report the first case of mechanochemistry being directly applied to synthesising a dinucleotide on a soluble support. While mechanochemistry eliminates the need to solubilise a supported oligomer in the solution phase for phosphoramidite coupling, the support still confers the benefit of being able to purify the product by precipitation or by simple liquid‐liquid extractions as needed. Furthermore, this study also explores the use of mechanochemistry in the initial functionalisation of the ionic liquid support with a nucleoside monomer. Abstract : Mechanochemistry was explored as an alternative to solvent‐based methods for oligonucleotide synthesis; first, for functionalising an ionic liquid support with a nucleoside, and second, for the coupling step of oligonucleotide synthesis. Advantages enabled by mechanochemistry are one‐pot syntheses, reduced volumes of solvents, use of less toxic solvents, and avoiding the need to fully solubilise the supported‐nucleoside during the coupling step.